Isolating Cu-Zn active-sites in Ordered Intermetallics to Enhance Nitrite-to-Ammonia Electroreduction - Jiao Lan; Zhen Wang; Cheng-wei Kao; Ying-Rui Lu; Feng Xie; Yongwen Tan (Nature Communications)
Abstract Electrocatalytic nitrite reduction to the valuable ammonia is a green and sustainable alternative to the conventional Haber-Bosch method for ammonia synthesis, while the activity and selectivity for ammonia production remains poor at low nitrite concentrations. Herein, we report a nanoporous intermetallic single-atom alloy CuZn (np/ISAA-CuZn) catalyst with completely isolated Cu-Zn active-sites, which achieves neutral nitrite reduction reaction with a remarkable NH3 Faradaic efficiency over 95% and the highest energy efficiency of ≈ 59.1% in wide potential range from −0.2 to −0.8 V vs. RHE. The np/ISAA-CuZn electrocatalyst was able to operate stably at 500 mA cm−2 for 220 h under membrane electrode assembly conditions with a stabilized NH3 Faraday efficiency of ~80% and high NO2 ‒ removal rate of ~100%. A series of in situ experimental studies combined with density functional theory calculations reveal that strong electronic interactions of isolated Cu-Zn active-sites altered the protonation adsorption species, effectively alleviating the protonation barrier of *NO2 and thus greatly facilitating the selective reduction of NO2 − into NH3.